Les relations entre les Zirides et les Fatimides à la lumière des documents épigraphiques - Lotfi Abdeljaouad (Revue des Mondes Musulmans et de la Méditerranée)
The Fatimid and Zirid inscriptions, listed on the monuments and in the cemeteries of Tunisia, constitute a real mirror on which are reflected the moments of stability or tension which governed the relations between Ifrīqiya and Cairo (10th-11th century). Indeed, the political titles and the shiite expressions, appearing in the official texts of the first Zirid sovereigns, testify their subjection to the Fatimids. Nevertheless, the disappearance of these titles and expressions, as well as the verbal inflation against the Fatimids observed in the texts of al-Mu‘izz b. Bādīs, give information on the progress towards the break and the declaration of independence. The total destruction or the partial hammering of the inscriptions recalling the shiite past are witnesses to the consumption of this break. These epigraphic data thus confirm the facts transmitted in the historic literature on this subject.